Surgical Pericardiectomy for Constrictive Pericarditis: A Single Tertiary Center Experience - Nachum, Eyal; Sternik, Leonid; Kassif, Yigal; Raanani, Ehud; Hay, Ilan; Shalabi, Amjad; Buber, Jonathan (The Thoracic and Cardiovascular Surgeon, 2018)
Background Although surgery is the sole therapeutic option for patients with constrictive pericarditis (CP), reports on high postoperative mortality rates have led to hesitant surgery referral. The aim of this study was to report the short- and long-term outcomes of surgical pericardiectomy (SP) from a large tertiary center.Methods Between January 2005 and January 2017, 55 consecutive patients underwent SP after comprehensive echocardiography, computed tomography, and hemodynamic studies. Detailed clinical, imaging, surgical techniques and follow-up outcomes were recorded.Results The most common etiology was idiopathic (n = 27, 49%) and 33 patients (60%) were in functional class 3/4. Sixteen patients (29%) underwent concomitant interventions during SP, and cardiopulmonary bypass (CPB) was used in these, as well as in four additional cases. Complete resection, independent of CPB, was achieved in 96%. One patient died during the index hospitalization, and four (7%) needed re-explorations due to bleeding. While 12 patients (22%) died during a mean follow-up of 52 ± 39 months, only 1 death was due to right heart failure. Functional class significantly improved (with a p-value < 0.001), diuretics were discontinued in all, and significant reductions of right atrial pressures were recorded. None of these outcomes differed as a result of concomitant interventions at the time of SP.Conclusion Short- and long-term outcomes of SP, performed either alone or concomitantly with other procedures, indicate high safety and favorable clinical and hemodynamic efficacy for the treatment of CP.
Keywords: pericardium; constrictive pericarditis; pericardiectomy